Pengaruh Motivasi Ustadz Terhadap Etos Belajar Santri Di Pondok Pesantren - Khasanah Uswatun; Uswatun Hasanah (Universitas Darul Ulum, 2022)
Motivation is the drive to behave. Motivation is a psychological process that reflects the attitudes, needs, perceptions, and decisions that occur in a person. Someone succeeds in learning because of encouragement or motivation from within that spurs the learning ethos is an attitude or behavior that grows in doing learning. This study aims to determine the effect of cleric’s motivation on students’ learning ethos. The subjects in this study were 40 studensts. The results of statistical test analysis using the Pearson Product Moment SPSS 20 foe Windows program showed the magnitude of the correlation between ustadz’s motivation and learning ethos was 0,408 with a significance of 0,009. So the relationship between ustadz motivation and learning ethos is very high, and Ha is accepted and Ho is rejected. Provisions for conclusion of acceptance and rejection of the hypothesis if it is significant below of equal to 0,05, then Ha is accepted and Ho is rejected.